EVALUASI PELAYANAN TOUR LEADER PT AL HIJAZ TERHADAP JAMAAH UMRAH PADA PT AL HIJAZ TAHUN 2019 - Kartika Utami; Wulandari Wulandari (Institut Agama Islam Negeri Metro, 2022)
Service is a series of activities needed by others in order to benefit from the service and provide satisfaction to the people served. One of the services offered by PT. Al Hijaz is the Tour Leader. The success of a trip depends on the services provided to pilgrims by the Tour Leader. The purpose of this study was to determine the services provided by the Tour Leader PT. Al Hijaz, to evaluate the service of Tour Leader PT. Al Hijaz towards Umrah pilgrims. The findings of this study indicate that PT. Al Hijaz's Tour Leader service can effectively serve pilgrims from departure to return to Indonesia. In terms of service, Tour Leader PT. Al Hijaz provides satisfying services for Umrah pilgrims, because it makes pilgrims feel safe, comfortable, and happy.